The determination of absorbed dose in femur bone marrow during x-ray radiography through fabrication of physical and digital femur phantoms - Dehyagani, Zaker Salehi (2013)
The Monte Carlo simulation codes, BEAMnrc, were used to simulate a diagnostic Xray generator. First and second HVL with particle spectrums of three X-ray beams, viz. 84, 103 and 127 kVp were obtained using BEAMnrc simulation, IPEM report SpekCal 78, and measurements. The results of BEAMnrc simulation and measurements were directly compared to those of IPEM report 78 and SpekCalc spectrum generator. The comparison revealed that the X-ray model used for simulation is accurate enough. A femur phantom using a real human femur and wax were then fabricated. The phantom was exposed to 85 kVp X-rays, 50 mAs at 100 cm SSD. TLD100H chips determined the absorbed dose values in different locations of the femur phantom while simulation results using DOSXYZ were obtained. Comparing the results demonstrated only 5% discrepancy between simulation result, 2.071 mGy, and TLD100H measurement result, 1.967 mGy, which implies good agreement between the results of simulations of X-ray radiation and measurements. The simulated absorbed dose inside the bone was observed to be 1.57 times higher than that of the surface of phantom. The DOSXYZ simulation was then carried out to simulate the *.egsphant file using DRR from CT scans of a real femur that seven bone marrow layers, 1 pm thick, were added to the location right after the cortical bone, and the precision of the absorbed dose values were then tested using 10 times repeat simulation. This repetition was carried out to ensure the validity of data for absorbed dose in the bone marrow. The dose in the bone marrow in the head of simulated femur, for 85 kVp, 50 mAs and 100 SSD was found to be 1.360 mGy, i.e., 36% of dose in cortical bone. The simulations were then carried out for three energies, viz. 102, 85 and 70 kVp, using different radiation filters and the absolute dose in the bone marrow were obtained for head and body of two real femurs. The results showed that when a constant mAs technique is used with 50 mAs, the dose to femur bone marrow ranges from 0.356 mGy to 2.403 mGy, with higher dose for higher kVp settings and when automatic exposure control, AEC, is used the relative absorbed dose ranges from 0.529 to 1, normalized at 70 kVp with 2.5 mm Al. It was observed for the AEC case that the dose is lower for higher kVp settings. For a typical femur radiography settings (USM setting), viz. 85 kVp, 6 mAs at 121.92 cm SID, the femur bone marrow dose obtained was 0.186 mGy. The results also showed that for femur radiography using the AEC technique, the maximum relative femur bone marrow dose for 10 ms are 0.0308 mGy, 0.0484 mGy and 0.0698 mGy for 70 kVp, 85 kVp and 102 kVp respectively when the default 2.5 mm Al was used.